Low Plasma Ergothioneine Predicts Cognitive and Functional Decline in an Elderly Cohort Attending Memory Clinics - Liu-Yun Wu; Cheuk Ni Kan; Irwin K. Cheah; Joyce Ruifen Chong; Xin Xu; Henri Vrooman; Saima Hilal; Narayanaswamy Venketasubramanian; Christopher P. Chen; Barry Halliwell; Mitchell K.P. Lai (MDPI AG, 2022)
Low blood concentrations of the diet-derived compound ergothioneine (ET) have been associated with cognitive impairment and cerebrovascular disease (CeVD) in cross-sectional studies, but it is unclear whether ET levels can predict subsequent cognitive and functional decline. Here, we examined the temporal relationships between plasma ET status and cognition in a cohort of 470 elderly subjects attending memory clinics in Singapore. All participants underwent baseline plasma ET measurements as well as neuroimaging for CeVD and brain atrophy. Neuropsychological tests of cognition and function were assessed at baseline and follow-up visits for up to five years. Lower plasma ET levels were associated with poorer baseline cognitive performance and faster rates of decline in function as well as in multiple cognitive domains including memory, executive function, attention, visuomotor speed, and language. In subgroup analyses, the longitudinal associations were found only in non-demented individuals. Mediation analyses showed that the effects of ET on cognition seemed to be largely explainable by severity of concomitant CeVD, specifically white matter hyperintensities, and brain atrophy. Our findings support further assessment of plasma ET as a prognostic biomarker for accelerated cognitive and functional decline in pre-dementia and suggest possible therapeutic and preventative measures.